The Evolution of Professional Training How Artificial Intelligence Technologies Can Accelerate the Learning. - Zaralli, Matteo (Routledge, Taylor & Francis Group, 2025)
This book is not just an analysis of the impact of emerging technologies on learning and professional development; it is also an invitation to reflect on the future of work, the nature of intelligence, and the evolution of human society in the digital age.
"A Productivity Press Book."
Description based upon print version of record.
Keywords: Professional education -- Technological innovations.; Educational technology.; Artificial intelligence -- Educational applications.; elektronické knihy; electronic books